Identifikasi Drug Related Problems (DRPs) Pada Pasien Congestive Heart Failure di Instalasi Rawat Inap RSUD Arifin Achmad Kota Pekanbaru - Sisri Novrita; Goldha Faroliu; Adrian Mulya; Anggy Saputri (LPPM Universitas Abdurrab, 2026)
Congestive Heart Failure is one of the leading causes of morbidity and mortality in Indonesia. Management of CHF patients often requires long-term combination therapy, which may increase the risk of Drug Related Problems (DRPs). This study aimed to identify DRPs in hospitalized CHF patients at Arifin Achmad General Hospital, Pekanbaru. This research applied a descriptive retrospective design using medical records of 216 patients from January to December 2024. The analysis was based on the 4T criteria (right drug, right dose, right indication, and right patient) and referred to the ACC/AHA guidelines. The results showed that most patients were male (65%) and belonged to the ≥60 years age group (49.1%). The most frequently prescribed therapies were furosemide (69%), bisoprolol (21%), and spironolactone (10%). Evaluation of drug rationality demonstrated that all patients (100%) received therapy according to the criteria right drug, right dose, right indication, and right patient. In conclusion, drug use in CHF patients at this hospital was rational and consistent with clinical guidelines, although further optimization of mortality-reducing drugs is still required.